The influence of Ag-Cu ions on natural biofilms of variable ages: Evaluation of MIC - Unsal, Tuba; Cansever, Nurhan; Ilhan-Sungur, Esra (ELSEVIER SCIENCE SA, 2022)
In this study, the biofilms at different ages formed on galvanized steel coupons in a simulating cooling tower water system were exposed to the Ag-Cu ions over 504 h and the changes in the structure of the biofilms were investigated using electrochemical, microbiological, and surface analyses. The effect of the Ag-Cu ions on the structure of the natural biofilm during the maturation process was evaluated for the first time in this study. Exposure to Ag-Cu ions changed the structure of the biofilm, reducing the concentration of carbohydrates in EPS, causing the shedding from the biofilm by disrupting/making weakening the integrity of the biofilm. After exposure to Ag-Cu ions, the biofilm turned into a heterogeneous, fissured-porous and sandy structure. In addition, in the absence of the ions and after exposure to the ions, the MIC behavior of galvanized steel with natural biofilm at different ages was evaluated using electrochemical and gravimetric tests. It was determined that the galvanized steel suffered to MIC and exposure to Ag-Cu ions increased the corrosion rate of it. Therefore, using of Ag-Cu ions at maximum concentration values (0.1 ppm Ag and 1.3 ppm Cu) suggested by EPA is not recommended to prevent MIC problem in cooling tower systems.
Keywords: Biofilm; Ag-Cu ions; EPS; Galvanized steel; Microbiologically influenced corrosion (MIC); MICROBIOLOGICALLY INFLUENCED CORROSION; STAINLESS-STEEL; MICROBIAL CORROSION; EXTRACTION METHODS; WATER; COPPER; SILVER; METALS; Biochemistry & Molecular Biology; Life Sciences & Biomedicine - Other Topics; Biophysics; Electrochemistry